Comparing Mathematics Achievement across High-Stakes Examinations: Evidence from WAEC/NECO and JAMB in Nigeria - Hassan Muhammad (International Journal of Education, Culture, and Society, 2026)
This study compares mathematics performance across essay-based secondary school examinations administered by the West African Examinations Council (WAEC) and the National Examinations Council (NECO) and the multiple-choice university entrance examination administered by the Joint Admissions and Matriculation Board (JAMB) in Nigeria. Using an ex post facto comparative design, archival mathematics examination records from 600 secondary school graduates were analyzed to determine the comparability of performance across the three examination systems. Mathematics performance in WAEC and NECO was operationalized using official grade classifications, whereas JAMB performance was assessed using subject-level aggregate score ranges. Data were analyzed through descriptive statistics, score standardization, and paired-samples t tests. The findings showed that a substantial proportion of candidates who attained credit-level grades in WAEC and NECO Mathematics obtained relatively low aggregate scores in JAMB Mathematics. Standardized mean comparisons further indicated that the same candidates performed better in WAEC and NECO than in JAMB, while the paired-samples analysis confirmed that the differences were statistically significant and associated with a large effect size. These results demonstrate systematic variation in mathematics performance between essay-based and multiple-choice high-stakes examinations. The study contributes empirical evidence to the mathematics education literature on assessment comparability in multi-examination contexts and underscores the need for cautious interpretation of examination outcomes generated by assessment systems with different formats and purposes, particularly when such results inform high-stakes educational decisions.